Penerapan Pembelajaran Bahasa Jawa dalam Membentuk Akhlakul Karimah pada Santri di Pondok Pesantren Syahid Al–Ma’arif Klaten - Mujibburrohman, Mujibburrohman; Hartadi, Hartadi (TSAQOFAH, 2026)
This study was motivated by the condition of santri at Pondok Syahid Al-Ma’arif Klaten in the 2022/2023 academic year, who came from diverse regions with different languages, habits, and characters that potentially give rise to conflicts, yet through appropriate education and methods can be guided to become santri who are polite in speech and behavior and diligent in worship. The study aimed to examine the implementation of Javanese language learning in shaping the akhlakul karimah of santri at Pondok Syahid Al-Ma’arif Klaten. A qualitative approach was employed, with data collected through observation, interviews, and documentation (photographs of boarding school activities and related records), involving the head of the pondok, Javanese language ustadz or teachers, and santri as research subjects. Data analysis was conducted using data triangulation and methodological triangulation techniques. The findings show that Javanese language learning for shaping akhlakul karimah is carried out through four main stages, namely integration into the boarding school curriculum, delivery of specific materials, habituation, and the application of educative sanctions. These four stages produced positive changes in the attitudes, speech, and persistence of santri in worship, as reflected in the data collected during the study. These findings affirm that systematically designed Javanese language learning makes a significant contribution to fostering santri’s akhlakul karimah in the pondok pesantren environment.